EFFECT OF DIFFERENT SOLUTIONS ON SEED GERMINATION AND GROWTH OF DIFFERENT SPECIES OF SEEDS - REVIEW (International Association of Biologicals and Computational Digest, 2022)
The germination of seeds in salt tress or in drought stress is possible with Hoagland’s solution by using growth regulators or growth hormones like Gibberellic acid solution, IAA, IBA, salicylic acid solution and etc. Hydropriming and Osmopriming is used to make the germination easy as it is regulating the moisture and temperature of seeds. Citric acid solution is mainly used to break seed dormancy. Polyethylene glycol (PEG) is the chemical solution which gives result as well. There are more ways for germination with CS/TPP nanoparticles and SLN with 1:100 & 1:1000 proportions with dilute solution.
Keywords: Gibberellic acid, IAA, IBA, Salicylic acid.